Heidegger from metaphysics to thought - Janicaud, Dominique, 1937-2002 (SUNY series in contemporary continental philosophy., 1995)
""Philosophy has come to an end" claimed Heidegger in the final posthumous interview he granted to Der Spiegel. The goal of Janicaud's chapters ("Overcoming Metaphysics?," "Heideggeriana," "Metamorphosis of the Undecidable," and the dialogue "Heidegger in New York") first of all is to clarify the project of "overcoming" metaphysics, a project that Heidegger himself recognized as open to innumerable misunderstandings. Is it really possible to surmount metaphysics, not by transgressing it, but by means of a patient elucidation of its key concepts? In the effort to underscore the originality of his own enterprise, doesn't Heidegger tend to project too harsh a dichotomy between the forgetfulness of Being and its authentic recollection? By raising these questions, Janicaud suggests that Heidegger himself does not elude the objections that he directs toward the great metaphysical thinkers." "The final recourse to dialogue in the midst of twentieth-century New York - a landscape intentionally "different" from one expectedly Heideggerian - intends to hint at another possibility than the indefinite deconstruction of metaphysical texts. It suggests new ways for thoughtful meditation and a new cast for action." "At the center of the book, Mattei evokes the "Heideggerian Chiasmus or the Setting-apart of Philosophy." Through an inquiry into the major Heideggerian texts produced between 1935 and 1969 and inspired by Holderlin's poetry, Mattei gradually detects the cosmic figure of the Geviert, the initial Fourfold where "earth and sky, the divine ones and the mortals" gather. Such a community, whose meaning Heidegger is the only one to decipher in our times, silently conforms to what is truly the archaic path to philosophy. The cosmic game of the Geviert also evokes, for Heidegger, the path of the Tao in the Chinese tradition. In this epoch characterized by the destruction of ontology, the two paths in which East and West meet may grant us moderns the hope one day of "dwelling" in the world."--Jacket